2020
DOI: 10.1080/16874048.2020.1789392
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of existing RC buildings by using autoclaved aerated concrete infill wall

Abstract: The objective of this study is to use autoclaved aerated concrete (AAC) for infill walls in existing buildings that are unsafe for earthquakes to increase their stiffness. The study included two topics; the first topic introduced six models using AAC in buildings resistance to earthquakes and the effect of self-weight of the buildings comparing bare frame clay partition masonry model (1), bare frame AAC partition masonry model (2), reinforced concrete frames clay infill wall model ( 3), reinforcement concrete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…From all the above research works, it is concluded that the RC frames increase their capacity to withhold lateral load which are infilled with AAC blocks [7]. The displacements of the RC and PC frames are reduced due to the instalment of masonry wall in the frames.…”
Section: Inferencementioning
confidence: 96%
See 1 more Smart Citation
“…From all the above research works, it is concluded that the RC frames increase their capacity to withhold lateral load which are infilled with AAC blocks [7]. The displacements of the RC and PC frames are reduced due to the instalment of masonry wall in the frames.…”
Section: Inferencementioning
confidence: 96%
“…The integrated construction method shows better result than non-integrated method. The higher aspect ratio specimen (narrow wall panel) produced more ductility and plastic energy.Okasha et al [7] developed models such as bare RC frame, RC frame infilled with clay blocks with and without anchorage, RC frame infilled with AAC blocks with and without anchorage are tested for failure load, displacement and ductility using ANSYS WORKBENCH 18.2. The models are developed to resist earthquake load.…”
Section: Rc Frames With Aac Block Infill Wallsmentioning
confidence: 99%
“…Yapılarda normal ağırlıklı harçlar yerine hafif harçlar kullanarak daha düşük ölü yük ile daha fazla enerji sönümlenebilir. Bununla birlikte, binanın ısı yalıtımına katkı da sağlanarak binaların termal konfor özellikleri iyileştirilebilir, yangınlara karşı daha güvenlikli yapılar elde edebilir, aynı zamanda binalarda ses yalıtım özellikleri de iyileştirilerek daha konforlu yapılar tasarlanabilmektedir [3,4,5].…”
Section: Introductionunclassified